2019
DOI: 10.1044/2019_jslhr-l-18-0418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Verb Overlap on Structural Priming in Dialogue: Implications for Syntactic Learning in Aphasia

Abstract: Purpose Although there is increasing interest in using structural priming as a means to ameliorate grammatical encoding deficits in persons with aphasia (PWAs), little is known about the precise mechanisms of structural priming that are associated with robust and enduring effects in PWAs. Two dialogue-like comprehension-to-production priming experiments investigated whether lexically independent (abstract structural) priming and/or lexically (verb) specific priming yields immediate and longer, last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 86 publications
(170 reference statements)
6
25
2
Order By: Relevance
“…Taken together, the current findings are consistent with previous studies on the explicit memory processes in structural priming, in that an explicit memory-related process contributes to both lexical-dependent structural priming ( [14,33,36]) and lexical-independent structural priming [29].…”
Section: Limited Memory Capacity In the Persistence Of Sentence Strucsupporting
confidence: 92%
See 4 more Smart Citations
“…Taken together, the current findings are consistent with previous studies on the explicit memory processes in structural priming, in that an explicit memory-related process contributes to both lexical-dependent structural priming ( [14,33,36]) and lexical-independent structural priming [29].…”
Section: Limited Memory Capacity In the Persistence Of Sentence Strucsupporting
confidence: 92%
“…Thus, the validity of this postulated explicit memory mechanism in structural priming was initially called into question (e.g., [28]). Nevertheless, a number of studies provide evidence for the possible involvement of explicit memory in structural priming ( [14,[29][30][31][32][33][34][35][36]). Importantly, several studies demonstrated that some effects of structural priming show characteristics that are analogous to a short-term memory effect ( [14,31,36]).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations